2008
DOI: 10.1111/j.1440-1584.2008.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviours and blood borne virus exposure for transient workers in rural Victoria

Abstract: Compared with nationally representative data, our study sample reported high rates of alcohol consumption at levels risky to health, illicit drug use and infrequent use of condoms. These results suggest that transient workers and their contacts would benefit from the targeted provision of harm-reduction services, with a particular focus on sexual behaviour and alcohol and drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The backpacker experience has been described as a transition or rite of passage, 18 which in the absence of ones’ own social and cultural constraints of country, community, and family, facilitates situational disinhibition 19 and sensation-seeking behaviors. 20 Not surprisingly, backpackers have a reputation for hazardous alcohol consumption 21,22 and frequent sex, 23 potentially with a greater likelihood of unprotected sex and multiple sexual partners when compared with short-stay holiday makers. 24 A cross-sectional study of British backpackers recruited from Sydney and Cairns hostel accommodation found that 40.3% drunk more than 5 times a week compared with 20.7% at home.…”
Section: Introductionmentioning
confidence: 99%
“…The backpacker experience has been described as a transition or rite of passage, 18 which in the absence of ones’ own social and cultural constraints of country, community, and family, facilitates situational disinhibition 19 and sensation-seeking behaviors. 20 Not surprisingly, backpackers have a reputation for hazardous alcohol consumption 21,22 and frequent sex, 23 potentially with a greater likelihood of unprotected sex and multiple sexual partners when compared with short-stay holiday makers. 24 A cross-sectional study of British backpackers recruited from Sydney and Cairns hostel accommodation found that 40.3% drunk more than 5 times a week compared with 20.7% at home.…”
Section: Introductionmentioning
confidence: 99%